Relações iatrogênicas na instituição hospitalar: uma abordagem psicológica - Nogueira, Ana Maria Sabrosa Gomes da Costa (1992)
This research aboards the study of the psychologist's development and the iatrogenic relations of the hospital lnstitution. A 'research-action', was put into practice during the years of 1989 and 1990 in a hospital unit of an offical health establishment of Rio de Janeiro state. As theoretic basis, the study supported itself on the thesis of Renê Barbier, Ivan Illich, H. Ferrari, Isaac Luchina, Michael Balint among others, in order to facilitate the comprehension of the meaning of the Instituion,of the iatrogenic relations and of the doctor-patient relation. Working in a team of professional people connected with the psychosomatie unit, we developed some activities which would refer to psychodinamic psychological aspects of the assistent relation between the interdisciplinary group and the patient, focussing more intimatly the role of the doctor and his ACT of assisting. Analising the General Hospital, as an Institution and all the relations which occured there, the research tried to identify the speaches and the performances which went through the different segments of the Institution itself. The dialetie approuch was the basic instrument of this work and the study of the clinic cases presented offered us, besides a reflexion on the every day hospital routine, a proposal of action based on the analysis of the same. Of the four occurences examined - two relating to children and two to adults, (tended in the infantile surgery ward and in the psychosomatic clinic respectively)it became more evident that the psychologist's performance must be faced not as an alternative of work, but as an indispensable function in the development of the doctor-patient relation.